Development of the composition of the tablets "Cardiosten" using the method of mathematical planning of the experiment - O. S. Kukhtenko; Ye. V. Hladukh (Zaporozhye State Medical University, 2019)
The aim of the work is devoted to the substantiation of the choice of excipients while the development of Cardiosten tablets with a dry extract from a mixture of medicinal plant materials of cardiological action, taking into account the application of the mathematical planning of the experiment. Materials and methods. Using the method of mathematical planning of the experiment (MPE), the influence of auxiliary substances on the technological properties of the granules with dry extract "Cardiosten" and tablets obtained from these granules was investigated. Fillers, sorbents (moisture regulators), structure-forming substances (disintegrating agents), binding substances and calcium stearate as a powdering agent (antifriction substance) were used as excipients. All groups of excipients (except calcium stearate) were divided into levels of factors, which were investigated by the four-factor experiment method based on a Greek-Latin square. The following indicators of granules and tablets based on dry extract "Cardiosen" were used as responses: bulk density g/cm3; mass flow for tableting, s/100g; mass loss during wetting and granulation, %; disintegration of tablets, min., abrasion of tablets, % and resistance of tablets to crushing, N. Results. In the course of the conducted research, the dependence of all responses on the above factors was determined according to the technological parameters of the tablet mass and finished tablets. Based on the analysis of the most effective levels of factors that had the maximum effect on the responses, the following substances were selected as further objects: Prosolv HD 90 (vehicle), Neosorb -100 (sorbent), polyplasdon XL10 (structuring agent) and HPMC solution as a binder. Conclusions. Using the MPE method, the most optimal excipients were selected for the production of tablets with a dry extract content of "Cardiosten". Based on the indicators of pelletized mass (bulk density, bulk flow, weight loss) and tablets (disintegration time of tablets, abrasion of tablets, resistance of tablets to crushing), the qualitative composition of auxiliary substances for the production of tablets by the method of wet granulation - Prosolv HD 90 (filler) was determined , Neosorb - 100 (sorbent), polyplasdon XL10 (structuring agent), HPMC solution (binding agent).